IMPLIKASI PENERAPAN BUDAYA MUTU BAGI PESERTA DIDIK DI SMA ISLAM AL-FALAH JAMBI - Jamilah Jamilah; Jamaluddin Jamaludidin; Riftiyanti Savitri (JMiE (Journal of Management in Education), 2020)
This study aims to describe the implications of applying quality culture in SMA Islam Al-Falah Jambi. This study uses qualitative methods. Data collection techniques using observations, interviews, and documentation. The results showed the application of quality culture has implications for students. Quality culture is applied through activities: 1) reading the Quran in class; 2) pray dhuha; 3) prayer dzuhur and asr congregation; 4) tadarus / reciting the Qur'an after dzuhur prayer; 5) memorize the surahs in the Qur'an; 6) mentoring; and 7) the night of the building of faith and taqwa (Mabit). This habituation helps students understand religious knowledge and be able to apply it well in their daily lives. Quality culture is also a characteristic for schools and becomes a system that forms learners into intelligent and skilled individuals in academic and non-academic activities while remaining faithful and godly to Allah Almighty.